An evaluation of international patient length of stay. (August 2014) - Bower, Lisa C.; Johnson, Tricia J.; Hohmann, Samuel F.; Garman, Andrew N.; Allen, Molly; Meurer, Steven J.
Abstract : While increasing attention has been given to patients traveling internationally for medical care, hospitals face unique challenges in caring for international patients that may increase hospital length of stay (LOS) and cost of care. The objective of this study was to evaluate whether there are variations in LOS by home region of origin for international patients traveling to the USA. This was a retrospective, cross-sectional study using patient-level discharge data from academic medical center members of University HealthSystems Consortium (UHC). The sample included 4517 international patients discharged between October 2008 and March 2012 from academic medical center members of UHC. Generalized linear regression models were fit to test the association between the LOS and country of home origin, controlling for patient demographic and clinical characteristics. Significant variation in LOS existed across countries of home origin. In the adjusted model, Saudi Arabian and Egyptian home origin were associated with the longest LOS (+3.6 and +3.4 days, respectively), followed by Kuwait (+2.6 days). Country of home origin was also associated with a varying impact on LOS in models that stratified by severity of illness (SOI) and clinical condition. Country of home origin was associated with LOS, even after accounting for patient demographic characteristics, SOI, and clinical condition. This suggests that non-clinical factors, such as differences in care coordination, may impact LOS. More work is needed to understand the underlying drivers of these differences, so that hospitals catering to international patients can develop interventions to improve the efficiency and quality of care provided.